2017
DOI: 10.1177/0891988717743589
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Nondemented Patients With Parkinson Disease: Motor Symptoms Versus Nonmotor Symptoms

Abstract: Both motor complications (UPDRS-IV) and NMS (NMSS) were associated with mortality at 4 years, being motor complications an independent predictor of it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Nonmotor symptoms are typically the main determinant of PD patients' quality of life [15], and certain nonmotor symptoms have been identified as risk factors for mortality [16]. Consistent with the present results, psychotic symptoms [17][18][19] and cognitive impairment/dementia [17,18,20,21] have previously been shown to be associated with an increased risk of death in patients with PD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nonmotor symptoms are typically the main determinant of PD patients' quality of life [15], and certain nonmotor symptoms have been identified as risk factors for mortality [16]. Consistent with the present results, psychotic symptoms [17][18][19] and cognitive impairment/dementia [17,18,20,21] have previously been shown to be associated with an increased risk of death in patients with PD.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have also suggested that an early development of autonomic dysfunction or individual autonomic abnormalities (including constipation, orthostatic hypotension, urinary symptoms, upper gastrointestinal tract symptoms, sweating abnormalities, and erectile dysfunction in males) are independent determinants of more rapid disease progression and shorter survival in patients already diagnosed with PD [22]. Constipation was also associated with a higher risk of death in diagnosed PD patients in Kaplan-Meier analysis [16]. However, to our knowledge, there are no previous reports on the direct association between pain and survival in PD.…”
Section: Discussionmentioning
confidence: 88%
“…The purpose of the current analyses was to assess predictors of increased mortality among ET cases. In this sense, the study is similar to numerous studies of Parkinson's disease from around the world that aimed to assess predictors of mortality, in which cases but no controls were enrolled (4347).…”
Section: Discussionmentioning
confidence: 99%
“…carry out ADL were at a higher risk of death in the short term (Santos-García et al, 2018). It is possible that targeted treatment of the separate DASH components would be beneficial, as both pharmacological (Schapira, Chaudhuri, & Jenner, 2017;Titova & Chaudhuri, 2018) and nonpharmacological (Cusso, Donald, & Khoo, 2016) treatments exist to ameliorate these symptoms.…”
Section: Discussionmentioning
confidence: 99%